(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
A series of novel chalcone derivatives were synthesized via Claisen–Schmidt condensation and evaluated through spectroscopic characterization and molecular docking studies. The synthesized compounds were characterized using Fourier Transform Infrared Spectroscopy (FT-IR), Proton Nuclear Magnetic Resonance (¹H NMR), and Mass spectroscopy. Molecular docking analysis was performed to evaluate binding interactions with the Epidermal Growth Factor Receptor (EGFR), a validated anticancer target. The docking results revealed favourable binding affinities ranging from –7.5 to –9.2 kcal/mol, supported by hydrogen bonding and hydrophobic interactions within the active site. The findings suggest that the synthesized chalcone derivatives possess promising anticancer potential and warrant further biological evaluation.